Genes : A Very Short Introduction - Slack, Jonathan (Oxford Oxford University Press, 2014)
In this Very Short Introduction to the gene Jonathan Slack explores the discovery, nature, and role of genes in evolution and development. Looking at how genes are understood as a concept, the nature of genetic variation, and how their mutation can lead to disease, this is an ideal guide for anyone curious about what genes are and how they work.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: Genes -- Genetics -- DNA